Determinants of internal vs. external CEO successions in Malaysian public listed companies - Ishak, Rokiah; Ku Ismail, Ku Nor Izah; Abdullah, Shamsul Nahar (Asian Academy of Management and Penerbit Universiti Sains Malaysia, 2012)
Following a CEO turnover, a company may select an internal or external successor. The objective of this study is to determine if firm performance, board attributes, ownership structure and incumbent power influence the decision of whether to elect an internal or external candidate. Results from logit regression analysis on 145 succession events over a four- year period (2002 to 2005) indicate that firms which are controlled by blockholders tend to select an outsider as the successor. Further, firms that are controlled by family members and disposition their predecessors are more likely to select an insider as the successor. However, firm performance does not affect the selection choice. As far as performance is concerned, this study supports the contingency view which believes that board of directors react differently to similar performance information due to several sociopolitical factors that may moderate the relationship between firm performance and CEO selection choice.